The Influence of Drug Abuse on the Young Generation - Kadir, Syukron Abdul; Doni, Christian; Rasyid, Muhammad Tebyan; Astuti , Nurmalita Kussuma; Arif, Nomensius; Ashar, Adinda Nasyuha Putri Cahyang (PT FORMOSA CENDEKIA GLOBAL, 2024)
Drugs are widely discussed and broadcast in mass media, such as television shows and social networks. Drugs are often discussed because of their abuse in society. Drugs cause many problems in communities such as Indonesia. Drug addiction cases often occur in Indonesia, ranging from minors, teenagers, adults to the elderly. In fact, illegal drugs or narcotics and dangerous drugs were initially only intended for anesthesia during surgery, for medicinal purposes or could also be used as rituals in ancient times, but as times change and people get older, drug abuse is becoming more common. The situation of drug abuse in society could be caused by the influence of the social environment, or even by oneself.